2019
DOI: 10.1136/bmjopen-2019-030252
|View full text |Cite
|
Sign up to set email alerts
|

Association between smoking and in-hospital mortality in patients with acute myocardial infarction: results from a prospective, multicentre, observational study in China

Abstract: IntroductionSmoking is a well-established risk factor for cardiovascular disease. However, the effect of smoking on in-hospital mortality in patients with acute myocardial infarction (AMI) who are managed by contemporary treatment is still unclear.MethodsA cohort study was conducted using data from the China AMI registry between 2013 and 2016. Eligible patients were diagnosed with AMI in accordance with the third universal definition of MI. Propensity score (PS) matching and multivariable logistic regression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 37 publications
0
12
0
2
Order By: Relevance
“… 17) 18) However, recent studies have shown that this hypothesized survival benefit in smokers with CAD no longer exists in the PCI era. 10) 11) 12) 13) 15) 27) Nevertheless, some studies have reported the “smoker's paradox.” 14) 16) These previous studies have investigated on shorter clinical outcomes compared with our results assessing 5-year clinical outcomes. 10) 11) 12) 13) Parasuraman et al 13) collected 12,656 patients with acute coronary syndrome following PCI to assess 30 day and 6 month mortality according to smoking status.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“… 17) 18) However, recent studies have shown that this hypothesized survival benefit in smokers with CAD no longer exists in the PCI era. 10) 11) 12) 13) 15) 27) Nevertheless, some studies have reported the “smoker's paradox.” 14) 16) These previous studies have investigated on shorter clinical outcomes compared with our results assessing 5-year clinical outcomes. 10) 11) 12) 13) Parasuraman et al 13) collected 12,656 patients with acute coronary syndrome following PCI to assess 30 day and 6 month mortality according to smoking status.…”
Section: Discussionmentioning
confidence: 95%
“… 8) 9) Previous studies have investigated the effects of smoking on clinical outcomes in patients with CAD. 10) 11) 12) 13) 14) 15) Although some studies have still reported smoker's paradox, 14) 16) numerous recent studies have shown similar or higher mortality in smokers compared to nonsmokers. 10) 11) 12) 13) 15) These discrepancies in study results are likely due to differences in study characteristics and covariate selection.…”
Section: Introductionmentioning
confidence: 99%
“…[29] The smoker's paradox whereby smokers have an increased risk of cardiovascular diseases but have lower mortality for in-hospital HF and PTCA patients has been previously reported. [3,7] This phenomenon may mislead the public on smoking cessation and many surgeons may ignore the importance of smoking cessation counselling.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Some subsequent studies also showed this so called 'smoker's paradox' phenomenon in different aspects. [3,[5][6][7] Coronary artery bypass grafting surgery (CABG) is an important method of treatment of CAD. From a surgical point of view, the impact of smoking on long-term postoperative outcomes have been reported, [2,8] while the association between smoking and in-hospital mortality in CABG patients remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…However, in 1973, Helmers et al reported that smokers had a lower risk of mortality than non-smokers [ 4 ]. Some subsequent studies also showed this so called ‘smoker’s paradox’ phenomenon in different aspects [ 3 , 5 7 ]. Coronary artery bypass grafting surgery (CABG) is an important method of treatment of CAD.…”
Section: Introductionmentioning
confidence: 94%